The Boundary Value Problem of the Equations with Nonnegative Characteristic Form. (25th July 2010) - Li, Limei; Ma, Tian
Abstract : We study the generalized Keldys-Fichera boundary value problem for a class of higher order equations with nonnegative characteristic. By using the acute angle principle and the Hölder inequalities and Young inequalities we discuss the existence of the weak solution. Then by using the inverse Hölder inequalities, we obtain the regularity of the weak solution in the anisotropic Sobolev space.